The Role of Interpersonal Communication in Students’ Self-control to Avoid Substance Abuse - Ade Tuti Turistiati; Baby Poernomo (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2020)
This study aims at answering the questions what causes many junior high school students fall into drug abuse, and what kind of treatment must be done so that students have self-control and are not subject to drug abuse. This study employed a phenomenological approach of a qualitative research design. In this study a semi-structured interview is used to understand how participants experienced the phenomenon. The research revealed that the interpersonal communication has a major role in students' self-control so as not to fall into drug abuse. This study contributes significantly to educational field particularly teachers in secondary schools so that it can be used as a reference to provide counseling to parents about the importance of interpersonal communication to build students’ self-control to prevent teens from falling into drug abuse.